2018
DOI: 10.5194/essd-2018-82
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A 16-year record (2002–2017) of permafrost, active layer, and meteorological conditions at the Samoylov Island Arctic permafrost research site, Lena River Delta, northern Siberia: an opportunity to validate remote sensing data and land surface, snow, and permafrost models

Abstract: Abstract. Most of the world's permafrost is located in the Arctic, where its frozen organic carbon con-tent makes it a potentially important influence on the global climate system. The Arctic climate appears to be changing more rapidly than the lower latitudes, but observational data density in the region is low. Permafrost thaw and carbon release into the atmosphere is a positive feed-back mechanism that has the potential for climate warming. It is therefore particularly im-portant to understand the links bet… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(51 citation statements)
references
References 40 publications
(49 reference statements)
1
50
0
Order By: Relevance
“…The second largest unit consists of Late Pleistocene to Early Holocene sandy sediments with low ice content and covers 23 % of the northwestern part (Schneider et al, 2009). Samoylov Island is part of the third unit, the Mid-to Late Holocene river terrace (Bolshiyanov et al, 2015), which makes up about twothirds of the delta (Schwamborn et al, 2002).…”
Section: Site Descriptionmentioning
confidence: 99%
“…The second largest unit consists of Late Pleistocene to Early Holocene sandy sediments with low ice content and covers 23 % of the northwestern part (Schneider et al, 2009). Samoylov Island is part of the third unit, the Mid-to Late Holocene river terrace (Bolshiyanov et al, 2015), which makes up about twothirds of the delta (Schwamborn et al, 2002).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Using a tiling approach to represent different parts of polygonal tundra allowed long-term (several decades) simulations on a landscape scale (several polygonal structures). We took advantage of a detailed in-situ data record from a site in the Lena River delta of Northern Siberia (Boike et al, 2018), which was used to provide model parameters and meteorological forcing data, as well as for comparisons between actual measurements and the simulation results. Our main objectives were:…”
Section: Introductionmentioning
confidence: 99%
“…All degradation stages described by Liljedahl et al (2016) can be found here, from non-degraded low-centered polygons to high-centered polygons with connected troughs (see Nitzbon et al, 2018). Between 1997 and 2017 the mean annual air temperature at the island was approximately -12.3 °C, with an annual liquid precipitation of 169 mm and mean end-of-winter snow depth of 0.3 m (Boike et al, 2018). The depth of zero annual amplitude is at 20.8 m, and has warmed from -9.1 °C in 2006 to -7.7 °C in 2017.…”
Section: Samoylov Island Northern Siberiamentioning
confidence: 86%
“…The island of Samoylov, located in the southern part of the delta, mainly consists of polygonal tundra surrounding a number of ponds and lakes (Fig. 1b;Boike et al, 2013Boike et al, , 2018). All degradation stages described by Liljedahl et al (2016) can be found here, from non-degraded low-centered polygons to high-centered polygons with connected troughs (see Nitzbon et al, 2018).…”
Section: Samoylov Island Northern Siberiamentioning
confidence: 99%
See 1 more Smart Citation